SP4 Medicines optimisation in action: the development of a dosing schedule and an extemporaneous formulation of pazopanib to treat a child with a recurrent desmoid tumour of the head and neck. Issue 9 (19th August 2020) - Holden, Victoria; Lowey, Andrew; Wilkins, Simone; Greer, Rachel
Abstract : Background: International experts recommended pazopanib to treat a 9 year old boy with a recurrent desmoid tumour. The tumour had progressed, leading to blockage of the airway and dysphagia. The child had previously received three lines of intravenous chemotherapy as well as surgery and local radiotherapy. Treatment intent was to give an effective oral therapy with minimal side effects aiming to maintain a reasonable quality of life and prevent further life threatening respiratory compromise. As the child had an unsafe swallow, the drug would need to be given via a gastrostomy tube. Pharmacy Input: A literature review was completed to establish the evidence to support the use and dose of pazopanib to treat desmoid type tumours in children. 1 2 Attempts made to find a commercial supply of pazopanib liquid yielded no results. In the absence of any data or experience from other principal children's cancer centres in the UK, first principles were used to review the physico-chemical properties of the molecule. Given the highly insoluble nature of pazopanib, an extemporaneous formulation for a pazopanib suspension was developed using Orasweet®, by adapting a formula suggested by the University of Oklahoma. 3 A risk assessment for the preparation process was completed and a mini isolator was re-commissioned for this purpose following appropriate testing by Quality Control. The Department of Pharmacology at Newcastle University were contacted to establish if therapeutic drug level analysis might be possible. Local approval for pazopanib use was obtained from the Drug and Therapeutic Group and an IFR was submitted to NHS England. Challenges: It was challenging to establish a dose regimen since the recommended paediatric dose from Phase I studies of pazopanib were dependent on the formulation used. 1 4 Pharmacokinetic sampling was not possible as no assay had been developed in the UK. The lack of availability of any commercial or compassionate use liquid preparation meant that the only way of giving the drug to this child was to prepare an extemporaneous preparation, despite paucity of evidence to support the stability of the preparation. Funding was not approved by NHS England; local funding was agreed. Outcome and Discussion: The child commenced treatment with the suspension in October 2018, administered via the gastrostomy tube. By July 2019 the patient had completed 10 cycles of therapy. Treatment was well tolerated. Minor side effects included abdominal and leg pain, vomiting, and a change in hair colour. The patient has had a good clinical response and a recent scan has shown substantial improvements in morphological appearance and size of the tumour. These results indicate that a locally prepared extemporaneous oral chemotherapy suspension can be successfully used to deliver treatment for a rare type of children's cancer. Pharmacy colleagues from across the department collaborated to facilitate this novel treatment option. References: Glade Bender J, Lee A, Reid J, et al . Phase I pharmacokinetic and pharmacodynamic study of pazopanib in children with soft tissue sarcoma and other refractory solid tumors: a children's oncology group phase I consortium report. JCO 2011;31 :3034–3043. Agresta L, Lee H, Turpin B, et al . Pazopanib therapy for desmoid tumors in adolescent and young adult patients. Pediatr Blood Cancer 2018;65 :e26968. Allen L Jr. Pazopanib 50 mg/ml oral suspension. US Pharm 2015;40 :61–62. Heath E, Forman K, Malburg L, et al . A phase I pharmacokinetic and safety evaluation of oral pazopanib dosing administered as crushed tablet or oral suspension in patients with advanced solid tumors. Invest New Drugs 2012;30 :1566–1574.